Pengaruh Anggaran Berbasis Kinerja dan Sumber Daya Manusia terhadap Kualitas Anggaran Pada Satuan Kerja Pemerintah Aceh - Aulia Grina; Zulkifli Umar; Budi Safatul Anam (BE-HISZ : Journal of Economics and Accounting, 2025)
This study aims to examine the effect of performance-based budgeting and human resources on budget quality in Aceh Provincial Government work units. A quantitative approach was employed using a survey method, with questionnaires distributed to 60 respondents directly involved in the budgeting process. The data were analyzed using multiple linear regression to test both partial and simultaneous effects among variables. The results indicate that performance-based budgeting and human resources have a positive and significant effect on budget quality, both individually and jointly. Performance-based budgeting shows a more dominant influence, followed by human resources. These findings suggest that outcome-oriented budgeting, supported by competent and capable personnel, enhances budget clarity, accountability, and effectiveness in regional financial management. This study provides practical implications for local governments to strengthen the implementation of performance-based budgeting and human resource development in order to improve public sector budget quality.